Keanekaragaman Kupu-Kupu (Lepidoptera) pada Empat Tipe Habitat di Hutan Lindung Gunung Klabat, Sulawesi Utara - Roni Koneri; Saroyo Saroyo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The objective of the research was to study the diversity of butterfly (Lepidoptera) in four habitat types  in  Mt Klabat protection forest, North Sulawesi. This research had been conducted over three months using a sweeping technique applied to follow the line transect length of 1000 meters at random in each habitat type (primary forest, secondary forest, gardens and shrubs). The results showed that there were 3 families namely Papilionidae, Nymphalidae and Pieridae, with the number of 29 species and 1014 individuals. The value of diversity based on Shannon and  Wienner diversity index and the highest was found in the garden (H = 2,24) followed by shrubs  (H = 2,12) and the lowest in secondary forests (H = 1,97). Based on the index Sorensen similarity (Cn) the composition of butterfly species found in primary forest has a high similarity value with secondary forest ((IS = 0,86), while the lowest among primary forest with garden (IS = 0,71). The result of This research is expected to be the basic data on butterfly diversity and effects of habitat changes on the diversity and distribution of butterfly in North Sulawesi